2016
DOI: 10.1007/s13361-016-1560-4
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid Capped Iron Oxide Nanoparticles as an Effective MALDI Matrix for Polymers

Abstract: Abstract. A new matrix-assisted laser desorption ionization (MALDI) mass spectrometry matrix is proposed for molecular mass determination of polymers. This matrix contains an iron oxide nanoparticle (NP) core with citric acid (CA) molecules covalently bound to the surface. With the assistance of additives, the particulate nature of NPs allows the matrix to mix uniformly with polar or nonpolar polymer layers and promotes ionization, which may simplify matrix selection and sample preparation procedures. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…To date a number of ionization techniques that belong to SALDI have been proposed,1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date a number of ionization techniques that belong to SALDI have been proposed,1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, ...…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles as typical, in treatable forms such as suspension liquids in order to ensure that the photon energies of the laser can act to desorp and ionize analytes 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. Indeed, the soft ionization laser method such as the original form of MALDI also belongs to this category 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although SPIONs are very attractive for biological studies, the use of this type of MNPs as matrix is severely limited due to insolubility in polar solvents. The results of some studies indicated that the SPIONs can be successfully utilized as matrix by changing the hydrophobic shell with water‐soluble ligands such as citric acid (CA) 21–24 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the importance of nanomaterials as outstanding MALDI matrices has become increasingly evident due to their unique physicochemical characteristics, such as excellent optical absorption, exceptional electrical properties, and low background interference 5057. Among these materials, carbon-based nanomaterials such as carbon nanotubes,58 carbon nanodots,59,60 carbon nanoparticles (CNPs),50,61 and graphene nanosheets (GNs)50,62,63 have attracted the most attention.…”
Section: Introductionmentioning
confidence: 99%
“…49 In recent years, the importance of nanomaterials as outstanding MALDI matrices has become increasingly evident due to their unique physicochemical characteristics, such as excellent optical absorption, exceptional electrical properties, and low background interference. [50][51][52][53][54][55][56][57] Among these materials, carbon-based nanomaterials such as carbon nanotubes, 58 carbon nanodots, 59,60 carbon nanoparticles (CNPs), 50,61 and graphene nanosheets (GNs) 50,62,63 have attracted the most attention. Compared to traditional organic matrices, these nanomaterials facilitate the desorption process and enhance MS signal intensity due to their superior interaction with biomolecules and efficient energy absorption.…”
Section: Introductionmentioning
confidence: 99%